2017
DOI: 10.3310/hta21320
|View full text |Cite
|
Sign up to set email alerts
|

A randomised controlled trial to assess the cost-effectiveness of intensive versus no scheduled follow-up in patients who have undergone resection for colorectal cancer with curative intent

Abstract: Background Intensive follow-up after surgery for colorectal cancer is common practice but lacks a firm evidence base. Objective To assess whether or not augmenting symptomatic follow-up in primary care with two intensive methods of follow-up [monitoring of blood carcinoembryonic antigen (CEA) levels and scheduled imaging] is effective and cost-effective in detecting the recurrence of colorectal cancer treatable surgically wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
55
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(58 citation statements)
references
References 78 publications
1
55
0
2
Order By: Relevance
“…The cost‐effectiveness and feasibility of such an intensive testing schedule needs to be evaluated fully. The mean direct NHS cost of CEA testing in the FACS trial was estimated at £7·50 per test (€8·40; exchange rate 13 January 2018), so the cost of the additional four tests in year 1 would be approximately £30 (€34), not taking account of subsequent price inflation. A recent study in the Netherlands, the CEAwatch trial, investigated an intensive follow‐up protocol that included more frequent CEA measurements (bimonthly), but fewer outpatient visits, which detected more curable recurrences than standard practice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The cost‐effectiveness and feasibility of such an intensive testing schedule needs to be evaluated fully. The mean direct NHS cost of CEA testing in the FACS trial was estimated at £7·50 per test (€8·40; exchange rate 13 January 2018), so the cost of the additional four tests in year 1 would be approximately £30 (€34), not taking account of subsequent price inflation. A recent study in the Netherlands, the CEAwatch trial, investigated an intensive follow‐up protocol that included more frequent CEA measurements (bimonthly), but fewer outpatient visits, which detected more curable recurrences than standard practice.…”
Section: Discussionmentioning
confidence: 99%
“…It was found that an additional US $60 700 (€51 465 in original article) would be needed to detect one additional patient with curable recurrent disease. Although the authors considered this to be acceptably low, until the quality‐of‐life and survival benefits of detecting recurrence before symptoms develop are known, definitive conclusions are not possible.…”
Section: Discussionmentioning
confidence: 99%
“…A comparison study of followup regimens after rectal cancer surgery with and without computed tomography over a course of almost 9 years elucidates the fact that it takes significant effort to collect comparative data in this context and the results are not definitive even with intensive planning and large patient numbers. The question could not be answered by this study [12]. In diagnostic radiology, every target variable shown in ▶ Table 2 can theoretically be an effectiveness parameter [13].…”
Section: Htas In Radiologymentioning
confidence: 79%
“…Weiterhin ist unsicher, ob durch eine intensivere Nachsorge eine Wirkung auf Lebensqualität (3 Studien, 2742 Teilnehmer), Angst (1 Studie, 180 Teilnehmer) oder Kosten (6 Studien, 1412 Teilnehmer) erzielt werden kann [26]. Nur die wenigen der nachgesorgten Patienten profitieren mit einem verbesserten 5-Jahres-Überleben, die in kurativer Absicht bei einem Rezidiv operiert werden konnten [27].…”
Section: Ct Und Nachsorge Beim Kolorektalen Karzinomunclassified